2017
DOI: 10.14295/bds.2017.v20i4.1482
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of splinted and unsplinted implant-retained maxillary overdentures without palatal coverage: A literature review

Abstract: <p>The palatal coverage is considered as an auxiliary element in the distribution of tensile strains on implant maxillary total prosthesis (implant overdentures) bases, either implant-supported or retained. However, complaints in some patients due to palate and phonetic impairment are constant. The palatal coverage removal would allow the improvement of these issues as well as pharyngeal control, salivary flow and hygiene. Thus, this literature review proposed to analyze the survival rates of dental impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Implants initially placed that were still present at follow-up were included and analyzed. The outcomes of included studies showed 18 lost implants on a total of 1164 implants in 291 patients rehabilitated with MIODs on four splinted implants [ 10 , 19 22 , 24 31 ] and 12 lost implants on a total of 1158 implants in 193 patients rehabilitated with MIODs on six splinted implants [ 10 , 19 22 , 24 , 28 , 33 ]. The pooled risk ratio for implant survival (RR = 0.71; CI = [0.34, 1.45]) showed no statistical differences between using 4 versus 6 splinted implants for supporting maxilla overdentures ( P = 0.34) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implants initially placed that were still present at follow-up were included and analyzed. The outcomes of included studies showed 18 lost implants on a total of 1164 implants in 291 patients rehabilitated with MIODs on four splinted implants [ 10 , 19 22 , 24 31 ] and 12 lost implants on a total of 1158 implants in 193 patients rehabilitated with MIODs on six splinted implants [ 10 , 19 22 , 24 , 28 , 33 ]. The pooled risk ratio for implant survival (RR = 0.71; CI = [0.34, 1.45]) showed no statistical differences between using 4 versus 6 splinted implants for supporting maxilla overdentures ( P = 0.34) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Patients usually require an overdenture without palatal coverage in order to increase comfort, taste, phonation, pharyngeal control, salivary flow, and hygiene. Another issue of discussion was the number of dental implants recommended to be installed to support a maxillary overdenture [ 33 ]. In the literature, it seems that the minimum favorable number to support a MIOD without palate coverage is four or six splinted implants [ 4 6 , 33 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation